Respuesta :
4-2y+(-8y)+6.5
A positive and a negative equal a negative.
4-2y-8y+6.5
Combine like terms.
-2y-8y= 10y
4+6.5= 10.5
-10y+10.5
That is the simplest form.
I hope this helps!
~kaikers
A positive and a negative equal a negative.
4-2y-8y+6.5
Combine like terms.
-2y-8y= 10y
4+6.5= 10.5
-10y+10.5
That is the simplest form.
I hope this helps!
~kaikers
Hey you start with the y's (-8y)+(-2y) thats would be -10y so whats left. 4+6.5 that would be 10.5 so your answer should look like this: -10y+10.5